Tatars in Soviet Turkestan: activities of intepreters and translators - Risligoy A. Rasulova (Историческая этнология)
The article highlights the role of Tatars in the propaganda and strengthening of the state administration of the Soviet power in Turkestan. The paper mentions facts which testify that in the given line of work representatives of the Tatar people were "necessary personnel" since they spoke not only the languages of the local population, but also Russian. The participation of Tatars in the system of territorial administration of the region, which was of great importance in establishing written and oral communications with the central authorities of the USSR, was very significant. It consisted in communicating decisions, orders, instructions and decrees of the Center to the local population. With the help of Tatars, the central authorities of the USSR became familiar with the content of legal and regulatory documents adopted in Turkestan. This counter-process, in accordance with the established rules of Soviet power, served to create a new system of governance in the region. The author studies the activities of Tatars in Soviet Turkestan from the point of view of the work of interpreters and translators (including literary translators). Based on historical data, analysis of literature and archival materials, the contribution of Tatar translators to intercultural communication, preservation of linguistic and cultural traditions has been shown. The paper discusses the role of Tatars in the formation of the language environment of Turkestan and the problems and difficulties that translators and interpreters encountered.